Diamide insecticide resistance in transgenic Drosophila and Sf9‐cells expressing a full‐length diamondback moth ryanodine receptor carrying an I4790M mutation. Issue 3 (3rd December 2021) - Richardson, Ewan; Homem, Rafael A; Troczka, Bartlomiej J; George, Christopher H; Ebbinghaus‐Kintscher, Ulrich; Williamson, Martin S; Nauen, Ralf; Davies, TG Emyr
Abstract: BACKGROUND: Resistance to diamide insecticides in Lepidoptera is known to be caused primarily by amino acid changes on the ryanodine receptor (RyR). Recently, two new target site mutations, G4946V and I4790M, have emerged in populations of diamondback moth, Plutella xylostella, as well as in other lepidopteran species, and both mutations have been shown empirically to decrease diamide efficacy. Here, we quantify the impact of the I4790M mutation on diamide activation of the receptor, as compared to alterations at the G4946 locus. RESULTS: I4790M when introduced into P. xylostella RyR expressed in an insect‐derived Sf9 cell line was found to mediate just a ten‐fold reduction in chlorantraniliprole efficacy (compared to 104‐ and 146‐fold reductions for the G4946E and G4946V variants, respectively), whilst in the field its presence is associated with a ≥150‐fold reduction. I4790M‐mediated resistance to flubendiamide was estimated to be >24‐fold. When the entire coding sequence of P. xylostella RyR was integrated into Drosophila melanogaster, the I4790M variant conferred ~4.4‐fold resistance to chlorantraniliprole and 22‐fold resistance to flubendiamide in the 3rd instar larvae, confirming that it imparts only a moderate level of resistance to diamide insecticides. Although the I4790M substitution appears to bear no fitness costs in terms of the flies' reproductive capacity, when assessed in a noncompetitive environment, it does, however, have potentially major impacts on mobility at both the larval and adult stages. CONCLUSIONS: I4790M imparts only a moderate level of resistance to diamide insecticides and potentially confers significant fitness costs to the insect. Abstract : The I4790M mutation on PxRyR imparts only a moderate level of resistance to diamide insecticides (as compared to G4946E or G4946V) and potentially confers significant fitness costs to the insect. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.